ETOS – innowacyjne narzędzie wspomagające nauczanie i uczenie się przedmiotów przyrodniczych - Basińska, Anna; Pietrala, Dawid; Cole, Ronald; Dziubalska-Kołaczyk, Katarzyna (Wydawnictwo Naukowe UAM, 2012)
The article presents the results of a series of studies conducted as part of the E-Tutor of Science project carried out at Adam Mickiewicz University, Poznań, Poland. The project aims to develop and test an innovative program of teaching support ETOS. The program aims to support science teaching and learning at two education levels: primary school (years 4-6) and junior secondary school (years 1-3). The scope of innovation in the project covers the incorporation of the Questioning the Author? classroom dialogue modeling method used for discussing science topics, virtual teachers (avatars), as well as introducing English into the science curriculum.
ETOS – an Innovative Tool for Enhancing Science Teaching and Learning
Keywords: education; science; multimedia; innovation; avatar; virtual teacher